Endoscopic Surgery Scope vs Scapel - Beeston, L (Operating Room Nurses Association of Canada Journal, 1993)
“Endoscopicsurgical principles and techniques are established methods of therapy in medical specialties, including gynecology, urology and gastroenterology.” (White, 1991) Technological advances in fiberoptics, camera lenses, lasers, insufﬂation equipment, coagu- lation devices, and accessory instruments have ex- tended the usefulness of endoscopic surgery. Endoscopic surgery has not been utilized to its fullest potential butwith the rapid progression of medical and surgical technology, the era of endoscopic surgery is nearing. The prediction is that 90% of all cholecystectomies, prostate cancer stagings, and se- lectlung procedures; 80% of kidney removals; 70% of hysterectomies, appendectomies, and hernia repairs; plus a potentially significant number of vagotomies and bowel resections will be done endoscopically within the next five years.(Burke, 1992)